Commercial Feed Substitution with Milkfish Waste Flour (Chanos chanos) Against Quail (Coturnix coturnix japonica) Egg White Index, Egg Yolk Index and Haugh Unit - Annisa Nur Aulia Purwantoro; Sri Hidanah; Dhandy Koesoemo Wardhana; Mohammad Anam Al Arif; Sunaryo Hadi Warsito; Widya Paramita Lokapirnasari (Universitas Airlangga, 2023)
Quail farming is quite developed, from year to year the population increases. The search for alternative feed as a substitute for feed sources is an effort by breeders to minimize feed costs. One alternative to replace feed ingredients can be fishery industry waste. Fishery waste that can be used as feed is milkfish waste (Chanos chanos). The purpose of this research was to determined the substitution of milkfish waste flour (Chanos chanos) at commercial feed to egg white index, egg yolk index and haugh unit. There are 20 quails (Coturnix coturnix japonica) at one day of age of four treatments and five replications. Each treatment consisted by five females. The treatment consisted of P0 with commercial feed 100%, P1 with commercial feed 98% + milkfish waste flour 2%, P2 with commercial feed 96% + milkfish waste flour 4% and P3 with commercial feed 94% + milkfish waste flour 6%. Based on results of the Analysis of Variance (ANOVA) there was not significantly different (p>0,05) on egg white index, egg yolk index and haugh unit. It can be concluded the substitution of commercial feed with milkfish waste flour (Chanos chanos) can maintain egg white index egg yolk index and haugh unit.